The Effect of Psychological Well-Being on Students’ Perception of Online Learning During the COVID-19 Pandemic - Rozali, Mohd Zulfadli; Mohd Samshul, Siti Nurafiqah; Abdul Rahman, Khairul Anuar (uthm, 2023)
The outbreak of COVID-19 has led to a global lockdown, and universities have shifted to online learning. Despite the various efforts made by universities for students' online learning during the pandemic, not much has been identified about how students perceived online learning and how it affected their psychological well-being (PWB). This study examines the differences between male and female students' perceptions of online learning during the pandemic. A quantitative research design was used to measure the effect of PWB among students on online learning during the pandemic. The population consisted of first-year students in Technical and Vocational Education and Training (TVET) from Bachelor of Technology programs; hence, 127 respondents were sampled. A validated researcher-developed questionnaire was used to test the reliability of the study. The collected data were analyzed using descriptive statistics. Spearman Rho correlation and Mann-Whitney U were used to test the hypotheses at a pvalue less than 0.05 level of significance. The findings revealed a PWB effect on students' perceptions of online learning. Meanwhile, there was no significant difference between genders affected by PWB in students' perceptions of online learning during the pandemic. Therefore, it is recommended to focus on one of the six elements of PWB regarding the perception of online learning among students.